Buku Ajar Beorientasi Literasi: Inovasi Pada Mata Kuliah Konsep Matematika Lanjut - Dian Kusmaharti; Via Yustitia (Universitas Mathla'ul Anwar Banten, 2020)
Mathematical literacy is a 21st century competency. The mathematics literacy of PGSD students at the PGRI Adi Buana University is not optimal. One of the innovations made is the development of literacy-oriented mathematics textbooks. The objectives of this study were to: (1) describe the process of developing literacy-oriented Advanced Mathematical Concepts textbooks; (2) describe the results of the development of the Mathematical Concepts textbook which is more literacy oriented. This type of research is development research with a 4D design model. The procedure for developing the defining, designing, and developing stages. The research data is in the form of documents of the development process, and the quality of textbook data from validators and potential users. Data analysis was carried out using quantitative quantitative techniques sequentially. The results showed that the results of the development of textbooks were valid and practical